Elections in Professional Medical Organizations and Examining Bodies - Haque, Anwar Ul (International Journal of Pathology, 2018)
This issue is not at all “Political” but rather verygenuine scientific and humane one. The ProfessionalOrganizations play key role in formulating nationalpolicies regarding medical education, training,research and healthcare. Obviously, quality of theProfessional Organizations and their input dependupon the quality of the people at the helms of affairsof these organizations